Visual snow syndrome: a comparison between an Italian and British population. (23rd July 2020) - Viana, M.; Puledda, F.; Goadsby, P. J.
Abstract : Background and purpose: Visual snow manifests as a pan‐field, dynamic visual disturbance described as continuous television static‐like tiny flickering dots. Current diagnostic criteria further require at least two additional symptoms for visual snow syndrome (VSS) from: palinopsia (afterimages and trailing); entoptic phenomena (floaters, blue field entoptic phenomenon, photopsia, self‐light of the eye); photophobia and nyctalopia. Our objective was to compare the phenotype of VSS in an Italian and British population. Methods: Patients with VSS were characterized clinically using the current criteria. An online survey was prepared in collaboration with the patient group Eye‐on‐Vision. Patients were directed to the site if they contacted us by email asking to be involved in research. After data collection, we compared the phenotypic characteristics of a subgroup of British versus Italian patients taking part in the survey. As we expected more responses from the UK, we matched 100 UK patients for gender and age with our Italian cohort. Results: Patients were enrolled from the UK ( n  = 100) and Italy ( n  = 100). The populations had similar demography. After multiple correction testing there were no differences in VSS features between the two groups. The same was true for the prevalence of migraine and previous use of recreational drugs. Conclusion: This is the first study comparing the phenotype of VSS between two distinct populations. Our findings suggest that the visual snow phenotype, as well as migraine comorbidity, is similar across the two groups.